Knowledge and attitudes of nurses regarding retinopathy of prematurity in neonatal intensive care units in Bhartpur, Chitwan, Nepal - Shrestha, Manisha (Journal of Chitwan Medical College, 2025)
Introduction: Retinopathy of prematurity (ROP) is a bilateral condition characterized by abnormal retinal vascularization in preterm infants, particularly those with very low birth weight. Nurses, as primary caregivers in neonatal units, and play a critical role in preventing ROP related blindness. Therefore, it is crucial to study their knowledge and attitude regarding ROP. The aim of this study was to document the knowledge and attitudes regarding ROP among nurses working in the neonatal intensive care units (NICU) of Bharatpur, Chitwan. Method: This was a quantitative, cross-sectional study using self-administered questionnaires to assess the knowledge and attitude among fifty-seven nurses working in the NICU of selected eight hospitals from Bharatpur, Chitwan; and was participated during continuing medical education (CME) session held on 28 Jun 2024. Descriptive and bivariate tests were calculated at p<0.05 using Microsoft Excel 2016 and Epi info version 7.02 respectively. The study was ethically approved. Result: Among 57 participating nurses in CME, the mean age of the participants was 27.11±5.73 years (ranging from 21 to 58 years), and all were female. Nearly three-fourth 44(77.19%) of the participants had average knowledge, while 9(15.79%) had good knowledge scores. The study revealed that 56(98.25%) of the nurses had a positive attitude towards ROP. Conclusion: The results of the study suggest that most nurses working in the NICU in Bharatpur had an average knowledge regarding the prevention, diagnosis, and treatment of ROP. Therefore, it is necessary to develop educational programs and competency-based training for neonate intensive care nurses about ROP.